Progesterone stimulates histone citrullination to increase IGFBP1 expression in uterine cells. Issue 2 (8th July 2021) - Young, Coleman H; Snow, Bryce; DeVore, Stanley B; Mohandass, Adithya; Nemmara, Venkatesh V; Thompson, Paul R; Thyagarajan, Baskaran; Navratil, Amy M; Cherrington, Brian D
Abstract : Peptidylarginine deiminases (PAD) enzymes were initially characterized in uteri, but since then little research has examined their function in this tissue. PADs post-translationally convert arginine residues in target proteins to citrulline and are highly expressed in ovine caruncle epithelia and ovine uterine luminal epithelial (OLE)-derived cell line. Progesterone (P4) not only maintains the uterine epithelia but also regulates the expression of endometrial genes that code for proteins that comprise the histotroph and are critical during early pregnancy. Given this, we tested whether P4 stimulates PAD-catalyzed histone citrullination to epigenetically regulate expression of the histotroph gene insulin-like growth factor binding protein 1 ( IGFBP1 ) in OLE cells. 100 nM P4 significantly increases IGFBP1 mRNA expression; however, this increase is attenuated by pre-treating OLE cells with 100 nM progesterone receptor antagonist RU486 or 2 µM of a pan-PAD inhibitor. P4 treatment of OLE cells also stimulates citrullination of histone H3 arginine residues 2, 8, and 17 leading to enrichment of the ovine IGFBP1 gene promoter. Since PAD2 nuclear translocation and catalytic activity require calcium, we next investigated whether P4 triggers calcium influx in OLE cells. OLE cells were pre-treated with 10 nM nicardipine, an L-type calcium channel blocker, followed by stimulation with P4. Using fura2-AM imaging, we found that P4 initiates a rapid calcium influx through L-type calcium channels in OLE cells. Furthermore, this influx is necessary for PAD2 nuclear translocation and resulting citrullination of histone H3 arginine residues 2, 8, and 17. Our work suggests that P4 stimulates rapid calcium influx through L-type calcium channels initiating PAD-catalyzed histone citrullination and an increase in IGFBP1 expression.